Development of an indoor tracking system - Wong, Daniel Yongjie (2014)
In the recent years, there has been an influx in the needs for indoor positioning and navigation across various industries. In this project, the aim is to implement a low cost and efficient solution based on current positioning technology namely using ZigBee along with the Arduino microcontroller. In order to estimate the tags within an acceptable range of error, various means such as statistical filters as well as trilateration is explored. In the report, factors such as path loss exponent that will affect this estimation are also discussed. A graphical user interface has been developed to show that that the location of the tags can be estimated and monitored with ease . Functionality tests have also been conducted to prove the results of these concepts.